Projek Penguatan Profil Pelajar Pancasila (P5) Dalam Menerapkan Ajaran Tri Hita Karana di SD Mahardika Denpasar - Ni Ketut Sukrawati (JAPAM (Jurnal Pendidikan Agama), 2025)
The curriculum is a component in education that serves as a guide in implementing learning.From time to time, changes in educational content continue to develop so that curriculum changesoften occur starting from the teaching plan, the Main Outline of the Teaching Program (GBPP),KTSP, the 2013 Curriculum and until now it has become the Merdeka curriculum with an additionalprogram called the Pancasila Student Profile Strengthening Project (P5). Problems discussed: (1)What are the steps for implementing P5?, (2) What are the obstacles in implementing P5?, (3) Howis the relevance of P5 to the concept of Tri Hita Karana teachings? The method used is a qualitativemethod. The results of the study show (1) the steps for implementing P5 are carried out in threestages, starting from the planning stage, implementation and evaluation stage. (2) Obstacles inimplementing P5 are based on two factors, namely internal factors and external factors. (3) Therelevance of P5 to the concept of Tri Hita Karana teachings, namely the dimensions of faith, devotionto God Almighty and noble morals are relevant to the teachings of parhyangan. The dimensions ofglobal diversity, mutual cooperation, independence, critical and creative reasoning are relevant tothe teachings of pawongan and palemahan.